Application of Big Data Mining, Machine Learning and Artificial Intelligence in Ore Deposits (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
With the advent of the era of big data AI, scientific research has moved into its fourth research paradigm: data-intensive science. Big data and machine learning have brought the study of ore deposits onto the artificial intelligence research stage. Big data mining, machine learning, and artificial intelligence algorithms and models have been applied to study multi-scale and multi-type ore deposit observation and exploration. The goal of this reprint is to highlight recent progress in the research and applications of big data and machine learning in the fields of ore deposit exploration.